2017
DOI: 10.15244/pjoes/65060
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Trichoderma on the Phytosanitary Status of Soil and Yield of Red Beets (Beta vulgaris L. subsp. vulgaris)

Abstract: Our article describes a study on the influence of mineral and organic fertilisation and three strains of Trichoderma sp. isolated from Polish soils on the count of moulds, including the Fusarium and Alternaria genera, as well as the soil fertility index and the yield of red beets. Apart from that, the aim of the study was to assess the interaction between Trichoderma sp. and plant pathogens. A field experiment was performed on haplic luvisols soil in 11 combinations: a control sample, a variant with a mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Samuels and Hebbar (2015) recorded Trichoderma populations ranging from 10 2 to 10 3 spores/g of soil or root, while Wolna-Maruwka et al (2017a) found natural populations of Trichoderma harzianum and Trichoderma atroviride occurring at 3.4 × 10 2 spores/g of dry soil in field experiments in Poland. In another study, Wolna-Maruwka et al (2017b), again only counting T. harzianum and T. atroviride, found 0.36 × 10 2 spores/g of dry soil in the control samples from their field experiment. Oskiera et al (2017), using a newly developed multiplex PCR technique, identified 10 3 -10 4 CFU/g of naturally occurring Trichoderma spp.…”
Section: Introductionmentioning
confidence: 94%
“…Samuels and Hebbar (2015) recorded Trichoderma populations ranging from 10 2 to 10 3 spores/g of soil or root, while Wolna-Maruwka et al (2017a) found natural populations of Trichoderma harzianum and Trichoderma atroviride occurring at 3.4 × 10 2 spores/g of dry soil in field experiments in Poland. In another study, Wolna-Maruwka et al (2017b), again only counting T. harzianum and T. atroviride, found 0.36 × 10 2 spores/g of dry soil in the control samples from their field experiment. Oskiera et al (2017), using a newly developed multiplex PCR technique, identified 10 3 -10 4 CFU/g of naturally occurring Trichoderma spp.…”
Section: Introductionmentioning
confidence: 94%